Tracking Virus-Specific CD4+ T Cells during and after Acute Hepatitis C Virus Infection - Michaela Lucas; Axel Ulsenheimer; Katja Pfafferot; Malte Heeg; Silvana Gaudieri; Norbert H. Grüner; Andri Rauch; J. Tilman Gerlach; Maria–Christina Jung; Roman Zachoval; Gerd R. Pape; Winfried Schraut; et al. (2007)
CD4+ T cell help is critical in maintaining antiviral immune responses and such help has been shown to be sustained in acute resolving hepatitis C. In contrast, in evolving chronic hepatitis C CD4+ T cell helper responses appear to be absent or short-lived, using functional assays.Here we used a novel HLA-DR1 tetramer containing a highly targeted CD4+ T cell epitope from the hepatitis C virus non-structural protein 4 to track number and phenotype of hepatitis C virus specific CD4+ T cells in a cohort of seven HLA-DR1 positive patients with acute hepatitis C in comparison to patients with chronic or resolved hepatitis C. We observed peptide-specific T cells in all seven patients with acute hepatitis C regardless of outcome at frequencies up to 0.65% of CD4+ T cells. Among patients who transiently controlled virus replication we observed loss of function, and/or physical deletion of tetramer+ CD4+ T cells before viral recrudescence. In some patients with chronic hepatitis C very low numbers of tetramer+ cells were detectable in peripheral blood, compared to robust responses detected in spontaneous resolvers. Importantly we did not observe escape mutations in this key CD4+ T cell epitope in patients with evolving chronic hepatitis C.During acute hepatitis C a CD4+ T cell response against this epitope is readily induced in most, if not all, HLA-DR1+ patients. This antiviral T cell population becomes functionally impaired or is deleted early in the course of disease in those where viremia persists.